INTRODUCTION TO ENVIRONMENTAL POLITICS FROM AN INDIAN PERSPECTIVE - Nahak, Duryodhan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the 21st century, environmental challenges have emerged as a widespread issue globally, taking on both transnational and global dimensions. However, there is no singular, centralized authority responsible for overseeing and regulating these environmental concerns on an international scale. Consequently, global governance in this realm is organized through a complex network of international treaties, multilateral institutions, non-governmental organizations, and multinational corporations. Within this context, India finds itself in a unique dual role in global climate politics. As a developing economy with relatively low historical and per capita emissions, it also represents a large and rapidly expanding economy facing increasing emissions. Like many other nations, India navigates a fragmented global framework defined by various international agreements. This paper presents an overview of environmental politics from an Indian perspective, emphasizing the distinctive challenges and opportunities India encounters in the realm of global environmental governance. Furthermore, the research investigates how India maneuvers through this intricate governance landscape, with a particular focus on the interplay between domestic policies and international obligations.